2018
DOI: 10.1021/acs.est.8b04865
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Evidence Shows Re-emission of Elemental Mercury Vapor Occurring after Reductive Loss from Foliage

Abstract: The mechanism of elemental mercury (Hg 0 ) re-emission from vegetation to the atmosphere is currently poorly understood. In this study, we investigated branch-level Hg 0 atmosphere-foliage exchange in a pristine evergreen forest by systematically combining Hg isotopic composition, air concentration and flux measurements to unravel process information. It is found that the foliage represents a diurnally changing sink for atmospheric Hg 0 and its Hg content increases with leaf age and mass. Atmospheric Hg 0 is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
206
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(230 citation statements)
references
References 54 publications
20
206
2
2
Order By: Relevance
“…This discrepancy can be explained by the fact that δ 202 Hg signatures measured in vegetation not only reflect the isotopic fractionation during foliar uptake, but also contain a re-emission component. Hg(II) reduction is expected to lead to more positive δ 202 Hg values in the residual, foliar Hg(II) fraction, irrespective of the reduction mechanism (Bergquist and Blum, 2007;Zheng and Hintelmann, 2010;Kritee et al, 2007;Jiskra et al, 2015). Re-emission of foliar Hg is supported by the observed negative shifts in odd-mass isotope MIF ( 199 Hg) in vegetation relative to 199 Hg of atmospheric Hg(0), which have been observed at Toolik Field Station (Olson et al, 2019) and elsewhere (Enrico et al, 2016;Demers et al, 2013).…”
Section: Hg Isotope Fractionation During Foliar Uptake Ofmentioning
confidence: 80%
“…This discrepancy can be explained by the fact that δ 202 Hg signatures measured in vegetation not only reflect the isotopic fractionation during foliar uptake, but also contain a re-emission component. Hg(II) reduction is expected to lead to more positive δ 202 Hg values in the residual, foliar Hg(II) fraction, irrespective of the reduction mechanism (Bergquist and Blum, 2007;Zheng and Hintelmann, 2010;Kritee et al, 2007;Jiskra et al, 2015). Re-emission of foliar Hg is supported by the observed negative shifts in odd-mass isotope MIF ( 199 Hg) in vegetation relative to 199 Hg of atmospheric Hg(0), which have been observed at Toolik Field Station (Olson et al, 2019) and elsewhere (Enrico et al, 2016;Demers et al, 2013).…”
Section: Hg Isotope Fractionation During Foliar Uptake Ofmentioning
confidence: 80%
“…In a recent study that employed stable Hg isotopes to measure exchange uxes for the rst time, the potential re-emission ux of Hg 0 from leaves was measured to be 30% in a forest canopy. 48 However, that study also reported a large uncertainty range (29-83%). Because of the current uncertainty in the re-emission ux and its temporal variation, we did not implement an immediate re-emission ux of Hg 0 from canopies in our model evaluation.…”
Section: Modeling Re-emission Of Hgmentioning
confidence: 87%
“…Second, the modeled daytime Hg 0 uptake needs to be reduced substantially, because daytime deposition is over-predicted in the modeled F net by a factor of up to 5 (summer at the grassland site). This adjustment can be implemented either by increasing the stomatal resistance R st term in eqn (2) or by application of a Hg 0 re-emission factor of stomatal Hg 0 uptake, as suggested by Yuan et al 48 We selected the rst option, although both methods would lead to similar reductions in stomatal Hg 0 uptake. Third, further improvement in model vs. measurement agreement can be reached by adjusting the soil Hg 0 re-emission scheme.…”
Section: Model Response To Adjusted Deposition Parameterization In Sumentioning
confidence: 99%
“…In this study, NEE of Hg 0 and CO 2 was measured concurrently with two independent EC systems over the intensively managed grassland used for forage production. Details on grassland species composition, harvest, and fertilization practices are described in Zeeman et al (2010), Merbold et al (2014) and Fuchs et al (2018). The tower for long-term EC greenhouse gas measurements was located between two adjacent grassland parcels (Fig.…”
Section: Site Description and Instrumentationmentioning
confidence: 99%
“…From the 20 Hz IRGA measurements, 30 min flux averages were calculated using the LI-COR EddyPro ® software. The 30 min CO 2 flux has been recorded continuously since 2005 (Eugster and Zeeman, 2006;Zeeman et al, 2010). The measured meteorological variables included temperature and relative humidity (Hygroclip S3 sensor, Rotronic AG, Switzerland), net allwave radiation (CNR 1, Kipp & Zonen B.V., Delft, Netherlands), incoming and reflected photosynthetic active radiation (PAR lite, Kipp & Zonen B.V., Delft, Netherlands), and precipitation (height of 0.5 m; tipping bucket rain gauge from LAMBRECHT meteo GmbH, Göttingen, Germany).…”
Section: Site Description and Instrumentationmentioning
confidence: 99%